CARDIORENAL SYNDROME IN CHRONIC HEART FAILURE: PATHOGENESIS, DIAGNOSTICS, PROGNOSIS AND OPPORTUNITIES FOR TREATMENT - E. A. Medvedeva; N. V. Shilyaeva; E. N. Iskhakov; Yu. V. Schukin (Российский кардиологический журнал, 2017)
The review focuses on cardiorenal syndrome developing in patients with chronic heart failure. The specifics of pathogenesis is discussed, as diagnostics and prognosis, with emphasis on the opportunities of modern biomarker strategy. The complicated cardiorenal issues are discussed and perspectives of their further exploration for treatment tactics in cohort of heart failure patients.